2018
DOI: 10.3390/molecules24010071
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Pharmacokinetic Studies on Complanatuside and Its Major Metabolites in Rats by UHPLC-Q-TOF-MS/MS and LC-MS/MS

Abstract: The metabolic and pharmacokinetic studies on complanatuside, a quality marker of a Chinese materia medicatonic, Semen Astragali Complanati, were carried out. The UHPLC-Q-TOF/MS (ultra-high performance liquid chromatography coupled with electrospray ionization tandem quadrupole-time-of-flight mass spectrometry) method was applied to identify the metabolites of complanatuside in rat plasma, bile, stool, and urine after oral administration at the dosage of 72 mg/kg. Up to 34 metabolites (parent, 2 metabolites of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…Peak 29 was tentatively identified as complanatuside with a molecular ion [M–H] − at 623.1616, and fragment ions at m / z 463.08559 [ 0,4 B -2H 2 O] − , m / z 337.09246 [M–ring B–2H 2 O] − , which further lost one molecule of water and gave m / z 315.05056. Other fragment ions, such as m / z 301.03066 [ 1,4 B–H 2 O–glucopyranosyl] − , and m / z 299.05594 [M–glucopyranosyl–glucopyranosyl] − , also further confirmed its potential structure [37]. Similar mass data about complanatuside was also reported in Lepidium draba L. [38].…”
Section: Resultssupporting
confidence: 68%
“…Peak 29 was tentatively identified as complanatuside with a molecular ion [M–H] − at 623.1616, and fragment ions at m / z 463.08559 [ 0,4 B -2H 2 O] − , m / z 337.09246 [M–ring B–2H 2 O] − , which further lost one molecule of water and gave m / z 315.05056. Other fragment ions, such as m / z 301.03066 [ 1,4 B–H 2 O–glucopyranosyl] − , and m / z 299.05594 [M–glucopyranosyl–glucopyranosyl] − , also further confirmed its potential structure [37]. Similar mass data about complanatuside was also reported in Lepidium draba L. [38].…”
Section: Resultssupporting
confidence: 68%
“…Complanatuside is a flavonol glycoside isolated from Astragalus complanatus , which is commonly used in traditional Chinese medicine clinics. Studies have shown that flavonoids from Astragalus complanatus exert anti-inflammatory, anticancer, and immuno-modulating activities ( Ng et al, 2014 ; Li et al, 2018 ; Yao et al, 2018 ). However, the anti-inflammatory effect and the protective effect of complanatuside on skin keratinocytes have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…That is commonly used as a traditional Chinese medicine in clinics. Flavonoids from Astragalus complanatus have been reported to exert inhibitory effects on inflammation and cancer ( Ng et al, 2014 ; Yao et al, 2018 ). In this study, IL-6, TNF-α, and IFN-γ were used to simulate “cytokine storm” to induce inflammatory injury in HaCaT cells.…”
Section: Introductionmentioning
confidence: 99%
“…Complanatuside has anti-inflammation, lipid-lowering and hepatoprotective properties. Complanatuside pharmacokinetic analysis has been developed and validated (Yao et al 2018). Eriocitrin flavanone has beneficial health effects and has antioxidant activity (Cesari et al 2020); as many of these compounds, low water solubility, stability and shelf life are major issues of eriocitrin.…”
Section: Luteolosidementioning
confidence: 99%